Restricted Use Pesticides for Use in Florida - Frederick M. Fishel (EDIS)
All pesticides are classified according to their toxicity, use pattern, and environmental effects. The two main classifications are unclassified use and restricted use, though unclassified pesticides are commonly referred to as general use pesticides. A restricted use pesticide is one that is for retail sale to and use by only certified applicators or persons under their direct supervision and only for those purposes covered by the applicator’s certification. This document will provide a listing of pesticide active ingredients registered in Florida that are classified as restricted and the reason(s) for the restricted use classification. This 4-page major revision was written by Frederick M. Fishel and published by the UF/IFAS Pesticide Information Office. https://edis.ifas.ufl.edu/pi073